2017
DOI: 10.1007/s13205-017-0724-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological and nitrogen metabolic enzyme analysis of psychrophilic and mesophilic Nostoc sp.: a comparative outlook

Abstract: Cyanobacterial diazotrophs play a significant role in environmental nitrogen economy despite their habitat either tropical or polar. However, the phenomenon by which it copes with temperature induced stress is poorly understood. Temperature response study of psychrophilic and mesophilic Nostoc strains explores their adaptive mechanisms. The selected psychrophilic and mesophilic strains were confirmed as Nostoc punctiforme and Nostoc calcicola respectively, by ultrastructure and 16S rDNA phylogeny. The psychrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…These phyla are usually associated with soil environment and root symbiosis ( Rudnick et al, 1997 ; Gtari et al, 2012 ). In addition to Nostoc , the nitrogen fixers Bradyrhizobium , Geobacter , Paraburkholderia , and Frankia ( Sellstedt and Richau, 2013 ; Calderoli et al, 2017 ; Thangaraj et al, 2017 ; Choi and Im, 2018 ; Hara et al, 2019 ) were abundant in all our studied systems ( Figure 7 ). The same dominant nitrogen fixers were found in Nash et al (2018) where Nostoc , Geobacter , Rhizobium , Polaromonas , and Frankia were found dominant in all three forefield systems.…”
Section: Discussionmentioning
confidence: 93%
“…These phyla are usually associated with soil environment and root symbiosis ( Rudnick et al, 1997 ; Gtari et al, 2012 ). In addition to Nostoc , the nitrogen fixers Bradyrhizobium , Geobacter , Paraburkholderia , and Frankia ( Sellstedt and Richau, 2013 ; Calderoli et al, 2017 ; Thangaraj et al, 2017 ; Choi and Im, 2018 ; Hara et al, 2019 ) were abundant in all our studied systems ( Figure 7 ). The same dominant nitrogen fixers were found in Nash et al (2018) where Nostoc , Geobacter , Rhizobium , Polaromonas , and Frankia were found dominant in all three forefield systems.…”
Section: Discussionmentioning
confidence: 93%
“…Cyanobacteria are ubiquitous in nature and their presence has long been reported in different soils (agriculture soils, rice fields, mines, desert lands, marshy soils) where they are responsible for bringing positive effects in different ecological situations [ 34 , 35 ]. Since the 1950s, application to soil of dry biomass (bio-inoculation) of different cyanobacteria, initially called “algalization”, has been shown to improve growth, health, and yields of various crops [ 36 , 37 ].…”
Section: Agricultural Use Of Cyanobacteria: From Biofertilizers To Biostimulantsmentioning
confidence: 99%
“…Marine cyanobacteria are considered to offer more advantages due to their high adaptability and applicability (Thangaraj et al 2017). These organisms are also known to sequester radionuclides through an extracellular metalbinding process that involves ionic interaction, precipitation, complexation, co-ordination, etc.…”
Section: Introductionmentioning
confidence: 99%